Evaluation of forest damage derived from the rearing of Apulo-Calabrese pig - Acciaioli A.; Grifoni F.; Fontana G.; Esposito S.; Franci O. (7th International Symposium on the Mediterranean Pig, 2012)
The Apulo-Calabrese is one of the five Italian native pig breeds, officially recognized. At the moment it is reared in 35 farms, 29 of them are localised in the Calabria region. The aim of this work was to assess animal management with particular attention to the forest grazing. The survey involved 20 farms and in 4 of them the forest damages in two seasons (summer and autumn) were evaluated. 80% of farms pastured forest all the year, 75% supplied concentrate to the animals irrespectively of pasture. 67% of farms pastured all the productive categories. The damage to trees from barking and root uncovering was higher in summer and decreased with the increased distance from the shelters. The slope of the soil increased the damage by uncovering (0.2% per degree). The most uncovered tree species were chestnut and phillyrea, while these most barked were holm, oak and phillyrea. Soil and litter were heavily damaged near the shelters (30.29% and 52.47%, respectively). Soil trampling and excavation damage were found in 31% and 36.5% of the experimental areas, respectively. Finally, the greatest damage was observed in the farms with the highest animal loading.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)